The long-lasting shadow of litter size in rodents: litter size is an underreported variable that strongly determines adult physiology - Marcela Parra-Vargas; Sebastien G. Bouret; Jens C. Bruning; Egberto G. de Moura; Theodore Garland, Jr.; Patricia C. Lisboa; Susan E. Ozanne; Mary-Elizabeth Patti; Andreas Plagemann; John R. Speakman; Manuel Tena-Sempere; Catherine Vergely; et al. (Molecular Metabolism, 2023)
Background/Purpose: Litter size is a biological variable that strongly influences adult physiology in rodents. Despite evidence from previous decades and recent studies highlighting its major impact on metabolism, information about litter size is currently underreported in the scientific literature. Here, we urge that this important biological variable should be explicitly stated in research articles. Results/Conclusion: Below, we briefly describe the scientific evidence supporting the impact of litter size on adult physiology and outline a series of recommendations and guidelines to be implemented by investigators, funding agencies, editors in scientific journals, and animal suppliers to fill this important gap.